Influence of Steel Fiber on Durability Performance of Concrete under Freeze-Thaw Cycles - Dong Li; Qing Guo; Shi Liu (Advances in Materials Science and Engineering)
To verify the steel fiber effect on durability properties of the concrete in cold regions, four types of steel fiber reinforced concrete were prepared, and the fiber dosage were 0, 20 kg, 40 kg, and 60 kg, respectively. The rapid freeze-thaw test was adopted to evaluate the frost resistance durability, and the evaluation indexes of the mass loss and the residual dynamic modulus of elasticity (RDME) the samples were compared, respectively. The frost damage of the matrix regarding the different freeze-thaw cycles (FTCs) was evaluated using the Weibull distribution. The capillary water absorption (CWA) experiments were also conducted corresponding to different freeze-thaw cycles (FTCs). The results revealed that the mass loss was not an effective index for frost damage evaluation of macro-steel fiber reinforced concrete. The FTCs corresponding to the loss of RDME to 60% were enhanced noticeably with the increase of fiber content. The relationship between the frost damage and the FTCs can be evaluated using the Weibull distribution. Compared with the PC, the frost resistance grade of the reinforced concrete with fiber dosage of 60 kg/m3 increased by 125%. After the frost action, the CWA capacity of concrete improved significantly, while, under the same FTCs, the CWA of the matrix decreased with the increment of macro-steel fiber dosage. The steel fiber showed a strong positive influence on enhancing the durability performance of concrete in cold region.